Factors Associated With Fecal Calprotectin Sample Collection Compliance: An IBD Center Quality Improvement Project. Issue 4 (3rd December 2022) - Fenton, David; Choi, Natalie K; Garcia, Nicole M; Dyer, Emma C; Cohen, Nathaniel A; Rubin, David T
Abstract: Background: Fecal calprotectin (Fcal) is a noninvasive, inexpensive biomarker of disease activity. However, patient compliance with this test is variable and incompletely described. We assessed compliance rates with Fcal tests and identified factors associated with noncompliance. Methods: A retrospective chart review of patients with inflammatory bowel disease (IBD) who had a Fcal test ordered through our center between August 2021 and December 2021 was conducted. Demographic, clinical, disease, and test-related information were recorded. Patients with incomplete Fcal orders were sent a survey to better understand their reasons for noncompliance. Simple statistical analysis and and multivariable logistic regression modeling were performed. Results: Of 303 patients, 165 (54.4%) had an order for Fcal. Of the Fcal tests ordered, 55 (33.3%) were not completed. Remission of IBD, no prior Fcal completion, and tests ordered at a distant site were all associated with test noncompletion. A multivariable logistic regression revealed that history of a prior completed Fcal test is associated with subsequent test completion (odds ratio = 2.1, 95% confidence interval 1.9–35.5, P = .004). Patients who did not complete the test described the pandemic and third-party testing center issues as the most common reasons for noncompliance. Conclusions: In this single center experience with Fcal testing in patients with IBD, we identified that a history of incomplete Fcal testing and distant location of lab testing were significantly associated with noncompletion of the test. We provide practical guidance for future utilization and compliance, including the impact of home-based testing. Lay Summary: Compliance to inflammatory bowel disease monitoring tools is important to assess patient inflammation levels and determine therapy regimens. Here, we find that patient noncompliance is associated with third-party testing centers, a lack of prior testing, and pandemic-related effects.